Dosage form developments of Polymer based drug delivery systems for Oral route (International Journal of Research in Pharmaceutical Sciences and Technology, 2024)
Scientists had created a unidirectional release sequence and sealed the other side of the patches with impermeable ethyl cellulose sheets. Other studies showed that the incorporation of drug-loaded microspheres into the patches, instead of direct loading of the drugs, can provide significantly enhanced control over the release behavior of the drug. Recently developed a lipophilic formulation (drug-in-oil formulation) to improve the compatibility of the system with intestinal cell lines and enhance the absorption of insulin. This formulation, however, lacked sufficient retention time at the targets. They eventually solved this problem by developing a bilayer patch comprised of a drug-impermeable layer to ensure unidirectional drug release and a layer of mucoadhesive to extend gastro-residence duration. The porous mucoadhesive layer was likewise impregnated with the drug-in-oil formulation. Although it has been more than two decades since the development of these oral devices, they have not attracted as much research attention as other designs, such as MPs Oral patches are most commonly used in the duodenum's early segments because solid boluses of digested food might remove the patch from the lumen wall in latter parts of the GI tract, considerably reducing the transitional period. Even in the duodenal part, the device needs strong bonding/binding with the mucus to avoid being washed away by gastric juice. Additionally, the mucus turnover cycle restricts the actual applicability of these devices for sustained delivery. This paper outlines similar latest technologies in polymer delivery systems for oral delivery.